1998
DOI: 10.1007/pl00001803
|View full text |Cite
|
Sign up to set email alerts
|

Spawning behaviour and sex hormone levels in adult and precocious brown trout (Salmo trutta L.) males and the effect of anosmia

Abstract: In the present experiment the behaviour and endocrine status of males of the brown trout, Salmo trutta L., (Salmoniformes: Salmonidae) were studied when males were kept in a stream tank with a nest digging female. Groups of mature adult males and precocious intact or anosmic male parr were placed with the nesting female so that the group resembled a natural spawning situation with big anadromous fish acting as dominant males and precocious parr acting as ''sneakers''. A control experiment was also run with onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 41 publications
5
26
1
Order By: Relevance
“…Among the other behavioural variables studied, the time of upstream swimming was reduced in exposed parr. There were some similarities with the results in the current study and those in Olsén et al (1998) with anosmic and intact male S. trutta parr. Those similarities are that intact male parr spent more time in close proximity to the female, completed more courting events and had higher levels of expressible milt than anosmic parr when placed with a female.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Among the other behavioural variables studied, the time of upstream swimming was reduced in exposed parr. There were some similarities with the results in the current study and those in Olsén et al (1998) with anosmic and intact male S. trutta parr. Those similarities are that intact male parr spent more time in close proximity to the female, completed more courting events and had higher levels of expressible milt than anosmic parr when placed with a female.…”
Section: Discussionsupporting
confidence: 88%
“…It is interesting that exposed male S. trutta parr in the stream tank had higher blood plasma levels of 11‐KT than the controls, but no differences were observed in frequency of aggressive acts. Previous studies have shown positive correlation between aggression and blood plasma androgen levels (Olsén et al , 1998). Sex hormone levels in plasma of the parr in the stream tank were much lower than in the priming experiment both in the exposed and the controls, c. 10 times lower of 11KT and half the concentration of 17,20β‐P, a difference that probably was caused by a difference in social environment.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…But to reproduce, trout must return to freshwater and compete for access to suitable spawning sites and mates. Interference competition generally favours large individuals (Olsén et al, 1998); however, in small shallow tributaries, small resident trout may have higher fitness because these habitats are less accessible for large individuals. Interference competition generally favours large individuals (Olsén et al, 1998); however, in small shallow tributaries, small resident trout may have higher fitness because these habitats are less accessible for large individuals.…”
Section: Influen Ce Of the S Pawning Hab Itat On Reproduc Tion Outcomementioning
confidence: 99%